Investigation of enterotoxigenic Escherichia coli (ETEC) vaccine candidates and identification of inhibitor of enterohemorrhagic Escherichia coli (EHEC) Type III secretion system effector NleB - Yang, Yang (Kansas State University, 2017)
Enterotoxigenic Escherichia coli (ETEC) is the most common cause of diarrhea in travellers and young children in developing countries. We previously characterized three vaccine candidates (MipA, Skp, and ETEC_2479) which effectively protected mice in an intranasal ETEC challenge model after immunization. However, these proteins are conserved not only in multiple ETEC isolates, but also in commensal bacteria. In this study, we examined the potential of these antigens to affect the host intestinal microbiota and subsequently found no significant impact on healthy of host after vaccination. In addition, we also optimized the types of adjuvants and forms of antigens and evaluated the efficacy in a mouse intranasal challenge model. Enterohemorrhagic Escherichia coli (EHEC) is an emerging zoonotic pathogen that cause global public health threads. EHEC possesses the potential to cause gastroenteritis, hemorrhagic colitis and hemolytic uremic syndrome (HUS), which may lead to renal failure. Type III secretion system (T3SS) is a hallmark of EHEC, characterized by the needle-like structure and a variety of effectors injected into host cells. NleB, one of T3SS effectors, is a glycosyltransferase with the ability to catalyze the transfer of N-acetyl-D-glucosamine (N-GlcNAc) to host proteins to suppress the activation of NF-kB signaling pathway. In this study, we employed luminescence-based glycosyltransferase assay and high-throughput screening using a chemical library of various compounds. A total of 128 chemicals was selected with significant inhibition on NleB glycosyltransferase activity for further pharmaceutical study as novel therapy against EHEC infection.
Keywords: E.coli; vaccine; inhibitor; Type Three Secretion System; NleB